Study Hasil Cabai Besar ( Capsicum annum L.) yang Ditanam Monokultur dan Tumpangsari dengan Tanaman Kacang Panjang (Vigna sinensis L.) pada Awai Musim Hujan - Djunaedy, Achmad (Universitas Trunojoyo Madura, 2008)
The objective of this research is tofind out the result of red pepper (Capsicum annum L.) grown monoculture and intercropping with legume in the early wet season. This research is conducted in Gili Timur sub-district of Kamal Bangkalan, with type of land Grumusol. This research is conducted in December 2003 up to March 2004. Design used in this research is complete random design (RAL). The treatment of this research consists of cropping red pepper grown monoculture and intercropping with legume in the early wet season. The findings showed that: 1) red pepper grown monoculture bloomingfaster and richer inflowers than intercropping, and the difference is significance, 2) number offruits grown monoculture was not significantl y different than grown intercropping, 3) percentage offlowers tofruits grown monoculture was smaller than intercropping, 4) red pepper grown monoculture produced fruits at average o/ 151.23 g, while grown intercropping produced fruits at average of 148.54 g.